A Novel Nickel-Catalyzed Domino Method for the Direct Synthesis of Symmetrical Disulfides Using Potassium 5-Methyl-1,3,4-oxadiazole-2-thiolate as a Sulfurating Reagent - Soleiman-Beigi, Mohammad; Mohammadi, Fariba (Synlett, 2015)
A simple, one pot, efficient, and novel protocol has been developed for the direct synthesis of symmetrical organic disulfides using a domino reaction between an aryl/alkyl halide and potassium 5-methyl-1,3,4-oxadiazole-2-thiolate in the presence of NiCl2 as catalyst. A variety of symmetrical aryl/alkyl disulfides can be obtained in moderate to excellent yields (up to 95%).
Keywords: nickel-catalyzed; disulfides; cross-coupling; 1,3,4-oxadiazole; sulfur-transfer reagents